2021
DOI: 10.3390/md19030168
|View full text |Cite
|
Sign up to set email alerts
|

New Polyketides from the Antarctic Fungus Pseudogymnoascus sp. HSX2#-11

Abstract: The species Pseudogymnoascus is known as a psychrophilic pathogenic fungus with a ubiquitous distribution in Antarctica. Meanwhile, the study of its secondary metabolites is infrequent. Systematic research of the metabolites of the fungus Pseudogymnoascus sp. HSX2#-11, guided by the method of molecular networking, led to the isolation of one novel polyketide, pseudophenone A (1), along with six known analogs (2–7). The structure of the new compound was elucidated by extensive spectroscopic investigation and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
0
26
1
Order By: Relevance
“…This greatly enriches the number and diversity of natural products of the genus Pseudogymnoascus. Except for antimicrobial activities of some of the previously obtained polyketides (Figueroa et al, 2015;Fujita et al, 2021;Shi et al, 2021), no other activities were found in Pseudogymnoascus in previous studies. This study is the first to identify secondary metabolites with cytotoxic activities (8 and 9) in Pseudogymnoascus.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…This greatly enriches the number and diversity of natural products of the genus Pseudogymnoascus. Except for antimicrobial activities of some of the previously obtained polyketides (Figueroa et al, 2015;Fujita et al, 2021;Shi et al, 2021), no other activities were found in Pseudogymnoascus in previous studies. This study is the first to identify secondary metabolites with cytotoxic activities (8 and 9) in Pseudogymnoascus.…”
Section: Discussioncontrasting
confidence: 53%
“…The extracts of some Pseudogymnoascus strains exhibit potent bioactivities, such as antimicrobial, herbicidal, and antitumoral activities (Henríquez et al, 2014;Gonçalves et al, 2015;Gomes et al, 2018;Ferrarezi et al, 2019). To the best of our knowledge, only 22 natural products, including 6 new compounds, were discovered from Pseudogymnoascus up to now (Figueroa et al, 2015;Guo et al, 2019;Fujita et al, 2021;Shi et al, 2021). More than 70% of the previously isolated structures belong to polyketides; others are alkaloids (13.6%), benzene derivative (9.1%), and fatty acid (4.5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pseudogymnoascus sp. HSX2#-11, an Antarctic fungus derived from a soil sample of the Fields Peninsula, which can produce various compounds according to our previous study [ 13 ], was further investigated to search for new secondary metabolites. As a result, one new pyridine derivative, 4-(2-methoxycarbonyl-ethyl)-pyridine-2-carboxylic acid methyl ester ( 1 ), together with one known pyrimidine, thymine ( 2 ) and eight known diketopiperazines ( 3 – 10 ) ( Figure 1 ), were isolated and identified from the potato dextrose agar (PDA) culture broth fermentative extracts of this strain.…”
Section: Introductionmentioning
confidence: 99%